Empty sella prevalence: step by step - Victoria B. Sharavii; Natalia A. Shnayder; Lada K. Sharavii; Marina M. Petrova; Regina F. Nasyrova (Russian Open Medical Journal)
An empty sella (ES), also known as an empty sella turcica (empty pituitary fossa) is defined as an intrasellar herniation of subarachnoid space within the sella which leads to flattening of the pituitary gland towards the posteroinferior wall. Purpose — to analyze studies of ES prevalence in the world. Methods — We carried out a systematic search in both Russian and English databases (E-library, PubMed, GoogleScholar, OxfordPress, ClinicalKeys) using keywords “empty sella”, “empty sella turcica”, “empty pituitary fossa”, “prevalence” and their combinations. The period of search: 2000-2020. It is also worth noting that earlier publications of historical interest were included in the review. Results — We have analyzed 23 studies. They can be roughly devided into two groups: the first group – screening studies of ES, the second group – targeted studies of ES.